Total vertebrectomy (Th2) and dissection of the subclavian artery for a superior sulcus tumor invading the spine: A case report. (2016) - Oka, Soichi; Matsumiya, Hiroki; Shinohara, Syuichi; Kuwata, Taiji; Takenaka, Masaru; Chikaishi, Yasuhiro; Hirai, Ayako; Imanishi, Naoko; Kuroda, Koji; Uramoto, Hidetaka; Nakamura, Eiichiro; Tanaka, Fumihiro
Highlights: The treatment of patients for lung cancer with vertebral body invasion remains challenging. We reported a case that total vertebrectomy (Th2) and dissection subclavian artery for lung cancer invading spine and subclavian artery. We experienced complete resected one case that tumor location and invading was very complicated. Abstract: Introduction: Surgery for primary lung cancer invading the spine remains challenging. Here, we present a case of superior sulcus tumor (SST) with vertebral invasion, successfully resected with total vertebrectomy (Th2) and dissection of involved apical chest wall and the subclavian artery (SCA). Presentation of case: A 62-year-old man was referred with the diagnosis of lung squamous cell carcinoma originating from left upper lobe (clinical stage IIIA/T4N0M0) involving the thoracic vertebrae (Th2) as well as the apical chest wall including three ribs (1st, 2nd and 3rd) and SCA. After induction concurrent chemo-radiotherapy, we achieved complete resection by three-step surgical procedures as follows: first, the anterior portion of involved chest wall including SCA was dissected through the trans-manubrial approach (TMA); next, the posterior portion of involved chest wall including ribs was dissected and left upper lobectomy with nodal dissection was performed through posterolateral thoracotomy; finally, total vertebrectomy (Th2) was performed through posterior mid-line approach. Discussion: This tumor was existence of anterior and posterior position in pulmonary apex region. So that, it is very important for complete resecting this complicated tumor to work out operation's strategy. Conclusion: Surgery may be indicated for SST invading the spine, when complete resection is expected.